Undocumented Students and Strategic Enrollment Management: Guidance and Considerations for Finance, Policy, and Inclusive Practice. Issue 1 (April 2017) - Serna, Gabriel R.
Abstract : This article addresses concerns related to college going and access for undocumented students related to the strategic enrollment management (SEM) function on college and university campuses. Utilizing theory and research related to college choice, SEM, and undocumented student issues, this review seeks to identify a set of guidelines aimed at helping SEM leaders and practitioners better serve undocumented students through the college choice process by highlighting considerations associated with finance, policy, and inclusive practice. Applying broad lessons from research to practice, the primary aim of this article is to better enable SEM professionals, some of whom may have little experience working with undocumented students, to better serve this population and the underlying goals of equity, access, and diversity.